'Child Competence' to Participate in and Consent to Health Treatment: A Foucauldian Discourse Analysis Investigating the Meaning of Competence - van Rooyen, Amanda (Auckland University of Technology, 2016)
Competence is a vital facet of the informed consent process. In New Zealand, despite some ambiguity in health legislation, children (less than 16 years of age) may give legally binding informed consent so long as they are competent to do so. The judgement of a child's level of competence is the responsibility of the attending health professional. Research studies have shown clear benefits to acknowledging children's competence to be included in and contribute to health discussions and decisions (Doyle, Lennox, & Bell, 2013; Gerison, 1994b). Unfortunately, New Zealand health legislation and policy do not give clear guidance on when or how to assess child competence and what makes a child a competent child. The purpose of this thesis was to analyse the meaning of competence and its effect on children's participation in, and consent to, health treatment. The aim of this research was to highlight the discourses that construct the idea of 'child competence'. Foucauldian discourse analysis was used to explore the meanings attributed to 'competent' and 'child competence' by New Zealand health professionals, government and society. In addition it aimed to highlight the possible effects this discourse has on children's participation in important health matters that affect them. Subsequently, it may assist in the development of theory, practice, and health policy related to competent children and their rights to participate in and give informed consent. Relevant New Zealand legislation, health policy and literature written from a historical standpoint have been analysed utilising Foucauldian theories of archaeology and genealogy; including the notions of power, knowledge, and the subject. The main findings of this study acknowledged the dominant subject positions held by health professionals and the legal system who imposed the legal version of the child competence discourse as authoritative. Factors contributing to the emergence of this discourse as authoritative in history included the requirement for children to be competent in order to enter adulthood and liberalism and individualism as the conditions required for its existence. The main innate conflict identified within this discourse included children's right to autonomous decision making versus adult's desire to protect them from undue harm. Through the analysis of what makes a child a competent child, life experience was noted as a marginalised discourse that had a large impact on the perceived level of children's competence. Adults' perception of competence as a binary with incompetence, rather than competence on a continuum, was noted as a possible barrier to children's participation in important health decisions. Lastly, and specific to New Zealand, the foundations of competence in individualism may have unexpected ramifications for many Māori and Pasifika children whose cultures are based on collectivism. Considerations for the implementation of competence assessments for this group of children are required so they too can realise the benefits of the recognition of competence. Further training for health professionals may be required to support the frequency and reliability of competence assessments. Research is required to develop a working definition of child competence in healthcare so that health professionals can more regularly, reliably and easily incorporate competence assessments into their practice. Inclusion of children's voices in the development of this working definition would demonstrate respect for their rights and perspectives on this matter.
Keywords: Children; Rights; Participation; Consent; Health; Medical